2019
DOI: 10.1111/nyas.14120
|View full text |Cite
|
Sign up to set email alerts
|

Inferior alveolar nerve transection disturbs innate immune responses and bone healing after tooth extraction

Abstract: Coordination between the nervous and innate immune systems to maintain bone homeostasis is largely uncharacterized. The present study investigated the sensory–immune interaction in resting alveolar bone and healing socket by surgical sensory denervation. Bone histomorphometry and immunohistochemistry showed that sensory denervation resulted in moderate suppression of bone remodeling, with a proinflammatory milieu manifested by increased neutrophil recruitment and possible alternations in macrophage phenotypes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 55 publications
0
13
0
Order By: Relevance
“…Previously, we transected the IAN outside the bony canal, which led to a breakdown of the distal nerve endings and a disturbed innate immune response along the resting bone surface 19,20 . In this study, IANI and IANT were performed in the intracanal region.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously, we transected the IAN outside the bony canal, which led to a breakdown of the distal nerve endings and a disturbed innate immune response along the resting bone surface 19,20 . In this study, IANI and IANT were performed in the intracanal region.…”
Section: Resultsmentioning
confidence: 99%
“…Among the neuropeptides, CGRP has been shown to play an important role in the growth, repair, and performance of the skeleton 21,22 . We found that local CGRP antagonism induced antianabolic and proinflammatory effects similar to those produced by sensory denervation, suggesting that sensory nerves may monitor the bony milieu by releasing CGRP 20 . CGRP can promote osteoblast differentiation and directly inhibit osteoclast formation by interacting with functional CGRP receptors expressed by these cells 21,22 .…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…In addition, deficiencies in sensory or sympathetic nerves result in inferior bone healing. [56][57][58][59] Nerve-resident cells are also important for bone regeneration. [60] Fibroblast-like mesenchymal cells, which differentiate and proliferate in damaged nerves, adopt the features of bone or cartilage cells and migrate into the damaged site to participate in healing of murine bone scratch injury.…”
Section: 3 Bone Regenerationmentioning
confidence: 99%
“…In addition, deficiencies in sensory or sympathetic nerves result in inferior bone healing. [ 56–59 ]…”
Section: Communication Between Nerves and Bonementioning
confidence: 99%